Przedsiębiorstwa ekonomii społecznej i ich wpływ na gospodarkę lokalną - Bogacz-Wojtanowska, Ewa (Social Enterprises and Their Impact on Local Economy, 2007)
The article presents the impact of social enterprises on local economy and local community. The following areas experienced positive impact: social capital, human resources development, and service development. The author also identified potential negative results of uncontrolled development of these enterprises particularly in areas such as: labour market, public subsidies, and commercial enterprises development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 229-236